Changing plant species composition and richness benefit soil carbon sequestration under climate warming. (2nd November 2022) - Yan, Yingjie; Niu, Shuli; He, Yicheng; Wang, Song; Song, Lei; Peng, Jinlong; Chen, Xinli; Quan, Quan; Meng, Cheng; Zhou, Qingping; Wang, Jinsong
Abstract: Anthropogenic warming and land‐use change are expected to accelerate global soil organic carbon (SOC) losses and change plant species composition and richness. However, how changes in plant composition and species richness mediate SOC responses to climate warming and land‐use change remains poorly understood. Using data from a 7‐year warming and clipping field experiment in an alpine meadow on the Qinghai–Tibetan Plateau, we examined the direct effects of warming and clipping on SOC storage versus their indirect effects mediated by plant functional type and species richness. We found that warming significantly increased SOC storage by 8.1% and clipping decreased it by 6.4%, which was closely correlated with the corresponding response of below‐ground net primary productivity (BNPP). We also found a negative correlation between SOC storage and species richness, which was ascribed to the increased BNPP via enhancing the dominance of grasses and decreasing species richness under warming. The lower SOC storage under clipping was caused by the clipping‐induced decrease in BNPP via weakening the dominance of grasses and increasing species richness. Our findings highlight that the SOC storage in this alpine meadow under climate warming and clipping was primarily governed by BNPP changes, which was mediated by changes in the dominance of grasses and species richness. Overall, our study demonstrates that shifting to the dominance of grasses and changing species richness would benefit soil C sequestration under climate warming, but this positive effect would be dampened by grazing or hay harvest. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.